Effect of Racial Inequities in Pre-Exposure Prophylaxis Use on Racial Disparities in HIV Incidence Among Men Who Have Sex with Men: A Modeling Study - Goedel, William C. (J Acquir Immune Defic Syndr, 2018)
BACKGROUND: Pre-exposure prophylaxis (PrEP) uptake has been slow among African American men who have sex with men (AAMSM) in the United States. We used an agent-based model (ABM) to simulate race-specific PrEP coverage to estimate their impact on racial disparities in HIV incidence among MSM in Atlanta, Georgia. METHODS: An ABM was constructed to simulate HIV transmission in a dynamic network of 10,000 MSM over ten years, beginning in 2015. We modeled a base scenario with estimated PrEP coverage of 2.5% among AAMSM and 5.0% among white MSM (WMSM). We then compared HIV incidence over ten years and calculated a disparity ratio of AAMSM to WMSM incidence rates across varying PrEP scale-up scenarios, with equal and unequal coverage among AAMSM and WMSM. RESULTS: Assuming current coverage remains constant, the model predicts HIV incidence rates of 2.95 and 1.76 per 100 person-years among AAMSM and WMSM respectively, with a disparity ratio of 1.68. If PrEP coverage were to increase six-fold without addressing inequities in PrEP uptake, the model predicts incidences of 2.65 and 1.34, corresponding to a mean decrease of 10.4% and 24.0% in HIV incidence, respectively. This stronger benefit for WMSM increased the disparity ratio to 1.98. Equal PrEP coverage among AAMSM and WMSM resulted in lower incidence rates overall with lower disparity ratios. CONCLUSION: Lower uptake among AAMSM relative to WMSM may limit the population-level impact of PrEP use among AAMSM, which may ultimately culminate in wider racial disparities in HIV incidence among MSM.